Corporate governance as a key aspect in the failure of worker cooperatives. (February 2022) - Basterretxea, Imanol; Cornforth, Chris; Heras-Saizarbitoria, Iñaki
The article analyses governance difficulties at Fagor Electrodomésticos, for decades the world's largest industrial cooperative, and sheds light on how the cooperative model and governance might have contributed to the firm's bankruptcy. The case study examines how the cooperative model influenced the speed and quality of decision making. The roles of the main cooperative governing bodies (the General Assembly, Governing Council and Social Council) are evaluated and their limitations to effectively supervise and work with management to make difficult strategic decisions. Several governance improvement measures are proposed in order to help other large cooperatives combine democratic control and economically sound governance.